2012
DOI: 10.1002/cne.23121
|View full text |Cite
|
Sign up to set email alerts
|

Connections of the lateral hypothalamic area juxtadorsomedial region in the male rat

Abstract: The connections of the lateral hypothalamic area juxtadorsomedial region (LHAjd) were investigated in a series of pathway-tracing experiments involving iontophoretic co-injection of the tracers Phaseolus vulgaris-leucoagglutinin (PHA-L; for outputs) and cholera toxin B subunit (CTB; for inputs). Results revealed that the LHAjd has connections with some 318 distinct gray matter regions encompassing all four subsystems-motor, sensory, cognitive, and behavioral state -included in a basic structure-function networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 182 publications
(321 reference statements)
0
12
0
Order By: Relevance
“…Comparing the current MRCC analysis to an earlier-alludedto hypothalamic structure-function model (11,35) facilitates exploration of possible functional interpretations. To elaborate, the earlier model identifies subgroupings based on structural and functional properties, giving five divisions: (i) a neuroendocrine motor zone associated with pituitary gland control; (ii) medial zone nuclei forming part of a putative behavior control column; (iii) a highly interconnected group of five rostrally located regions and the three regions of the DMH that together are considered to form a theoretical "visceromotor network" (35) for generating patterned autonomic and neuroendocrine motor output; (iv) a periventricular region related to (and possibly expanding) the visceromotor network, defined essentially by what remains of the periventricular and medial zones after subtracting the neuroendocrine motor zone, medial zone nuclei, and visceromotor network; and (v) a lateral zone associated prominently with the behavior control column, which is supported by more recent data (18)(19)(20)36).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Comparing the current MRCC analysis to an earlier-alludedto hypothalamic structure-function model (11,35) facilitates exploration of possible functional interpretations. To elaborate, the earlier model identifies subgroupings based on structural and functional properties, giving five divisions: (i) a neuroendocrine motor zone associated with pituitary gland control; (ii) medial zone nuclei forming part of a putative behavior control column; (iii) a highly interconnected group of five rostrally located regions and the three regions of the DMH that together are considered to form a theoretical "visceromotor network" (35) for generating patterned autonomic and neuroendocrine motor output; (iv) a periventricular region related to (and possibly expanding) the visceromotor network, defined essentially by what remains of the periventricular and medial zones after subtracting the neuroendocrine motor zone, medial zone nuclei, and visceromotor network; and (v) a lateral zone associated prominently with the behavior control column, which is supported by more recent data (18)(19)(20)36).…”
Section: Discussionmentioning
confidence: 69%
“…Hypothalamic cytoarchitecture is highly differentiated, generally more so than other central nervous system (CNS) divisions (17). Illustrative of hypothalamic connectional complexity, one of its major subdivisions-the lateral hypothalamic area (LHA)contains the most highly connected CNS regions identified to date [in terms of macroscale connections (macroconnections)] (18)(19)(20).…”
mentioning
confidence: 99%
“…In rats, orexin neuron cell bodies are located in the perifornical nucleus, and in the dorsal and lateral hypothalamic areas (LHA; Peyron et al, 1998; Nambu et al, 1999). Interestingly, it has been suggested that differentiations in each LHA are involved in the control of specific behavior, with the involvement of the LHA suprafornical region in the control of food intake behavior (Hahn and Swanson, 2010, 2012). High resolution studies of the orexin neuron population in the LH have been carried out (Swanson et al, 2005) showing the extreme complexity of this brain area.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that it could act by modulating olfactory sensitivity according to satiety (Aimé et al, 2007; Julliard et al, 2007; Prud’homme et al, 2009, for review: Palouzier-Paulignan et al, 2012). The cytological, connectional (Hahn and Swanson, 2010, 2012), immunohistological, and molecular (Peyron et al, 1998; Sakurai et al, 2005; Swanson et al, 2005) characterization of the lateral hypothalamus (LH) has already been performed. These studies suggest the existence of a functional loop between olfactory centers and the hypothalamus, which could explain the modulation of olfaction depending on energy balance.…”
Section: Introductionmentioning
confidence: 99%
“…The anterograde tracers may be used to establish the anatomical relationships between various components of neural networks when combined with retrograde tracing methods. Both PHA-L and the high molecular weight BDA 10 kDa are excellent anterograde tracers that have been used in many tracing studies reported to date (Krajewski et al 2010;Hahn & Swanson, 2012). These tracers are delivered stereotactically into the desired location to label neuronal cell bodies and axons selectively.…”
Section: Projections Of Arn and Rp3v Kisspeptin Neurons Delineated Bymentioning
confidence: 99%